A Phase 3 Study of Enarodustat (JTZ-951) in Japanese Hemodialysis Patients for Treatment of Anemia in Chronic Kidney Disease: SYMPHONY HD Study - Tadao Akizawa; Masaomi Nangaku; Takuhiro Yamaguchi; Ryosuke Koretomo; Kazuo Maeda; Yuya Miyazawa; Hideki Hirakata (Karger Publishers, 2021)
Introduction: Enarodustat (JTZ-951) is a new oral hypoxia-inducible factor-prolyl hydroxylase inhibitor for the treatment of anemia in chronic kidney disease (CKD). We conducted a phase 3 study to compare the efficacy and safety of enarodustat with darbepoetin alfa (DA) in Japanese anemic patients with CKD receiving maintenance hemodialysis. Methods: Subjects receiving maintenance hemodialysis were randomly assigned at a 1:1 ratio to receive oral enarodustat once daily or intravenous DA every week for 24 weeks with dose adjustment every 4 weeks to maintain hemoglobin (Hb) within a target range (≥10.0 to <12.0 g/dL). The primary efficacy endpoint was difference in mean Hb level between arms during the evaluation period defined as weeks 20-24 (noninferiority margin: −1.0 g/dL). Intravenous iron preparations were prohibited during the screening period and during weeks 0-4. Results: The mean Hb level of each arm during the evaluation period was 10.73 g/dL (95% confidence interval [CI]: 10.56, 10.91) in the enarodustat arm and 10.85 g/dL (95% CI: 10.72, 10.98) in the DA arm. The difference in the mean Hb level between arms was −0.12 g/dL (95% CI: −0.33, 0.10), confirming the noninferiority of enarodustat to DA. The mean Hb level of each arm was maintained within the target range during the treatment period. Increased total iron-binding capacity and serum iron and decreased hepcidin were observed through week 4 in the enarodustat arm albeit after switching from erythropoiesis-stimulating agents. No apparent safety concerns of enarodustat were observed compared with DA. Discussion/Conclusion: Enarodustat was noninferior to DA for the treatment of anemia in CKD patients receiving maintenance hemodialysis and was generally well tolerated over 24 weeks.